Double Columnar Structure with a Nanogradient Composite for Increased Oxygen Diffusivity and Reduction Activity. Issue 17 (17th July 2014) - Ju, Young‐Wan; Hyodo, Junji; Inoishi, Atsushi; Ida, Shintaro; Tohei, Tetsuya; So, Yeong‐Gi; Ikuhara, Yuichi; Ishihara, Tatsumi
<x xml:space="preserve">Abstract</x> The cathodic performances that can be achieved in solid oxide fuel cells (SOFCs), particularly in terms of oxygen diffusion, need to be improved so that high power densities can be produced at intermediate temperatures. Here, to improve the cathodic performance, a double columnar functional interlayer (DCFL) consisting of Sm0.2Ce0.8O2−δ (SDC) and Sm0.5Sr0.5CoO3−δ (SSC) is fabricated between a La0.9Sr0.1Ga0.8Mg0.2O3−δ electrolyte film and a SSC cathode film with pulsed laser deposition. The DCFL has a rough surface morphology consisting of nanosized grains (with diameters less than 5 nm), and it is formed of small columns that grow at an angle of ca. 45° from the substrate. Inserting the DCFL causes the electrical conductivity of the cathode to increase significantly, and the power density obtained by using it in a metal‐supported SOFC is increased. Atomic resolution scanning transmission electron microscopy (TEM) images and density functional theory calculations confirm that the samarium atoms in the SDC columns and cobalt atoms in the SSC columns are located at the interfaces between SDC and SSC columns. Therefore, it is possible a SmCoO3−δ nanogradient is formed, which may cause lattice distortions. The 18O2 concentration is actually much higher in the DCFL than in either of SSC or SDC films.